(untitled) (International Journal of Nursing Education, 2025)
Administrators play a pivotal role in empowering staff and influencing staff nurse’s work engagement and intent tostay in their organization to ensure positive organizational and patient outcomes. A study was done to find out the relationship between nurse’s empowerment behaviour with their job satisfaction, occupational stress and professional commitment among staff nurses (N=428) in selected hospitals, Coimbatore, Tamilnadu, India by using nonexperimental design. The findings of this study revealed that majority 319 (74.5%) had adequate nurses empowerment behavior, 224 (52.3%) had moderate satisfaction, 218 (50.9%) of subjects had mild stress and 243 (56.8%) of them had moderate professional commitment. It was observed that the calculated correlation value between nurse empowerment behavior and job satisfaction is r=0.386 shows a positive correlation, nurse empowerment behavior and occupational stress value wasr=-0.150 shows a negative correlation, nurses empowerment behavior and professional commitment value was r=-0.041 shows a no correlation, job satisfaction and occupational stress value was r=-0.432 shows a negative correlation, job satisfaction and professional commitment value was r=-0.055 shows a no correlation, occupational stress and professional commitment value was r=0.296 shows a positive correlation. This study concluded that the nurse administrator should take a holistic approach in their endeavor to increase job satisfaction & professional involvement and reduce occupational stress among staff nurses which will enable better patient outcome.